EMERGENCY COMMUNICATION SYSYTEM FOR NATURAL DISASTER USING MANET - Babu J, Dilish; Kumar, Dr. S Mohan (IJRDO -Journal of Computer Science Engineering, 2016)
Regular fiasco stricken numerous ranges of world consistently, effectiveness of salvage operation is exceptionally basic to life sparing of caught casualties. Be that as it may, cell correspondence framework is generally slammed when calamity hits a territory which makes coordination extremely troublesome among salvage volunteer groups. Tragically a large portion of existing crisis correspondence framework may not be plausible. In this paper, we proposed idea of half and half cell MANET engineering which utilize working cell base station in the event that they are not slammed. We additionally give a directing plan for this crisis situation which effectively uses accessible correspondence and vitality assets of gadgets. The proposed crisis correspondence design knows about portability of gadgets furthermore bolster self sorting out component of MANET. This correspondence model can be setup in catastrophe hit zone inside couple of hours